Frequent occurrence of highly expanded but unrelated B-cell clones in patients with multiple myeloma. - Jitra Kriangkum; Sarah N Motz; Carina S Debes Marun; Sandrine T Lafarge; Spencer B Gibson; Christopher P Venner; James B Johnston; Andrew R Belch; Linda M Pilarski (PLoS ONE, 2013)
Clonal diversity in multiple myeloma (MM) includes both MM-related and MM-unrelated clonal expansions which are subject to dominance exerted by the MM clone. Here we show evidence for the existence of minor but highly expanded unrelated B-cell clones in patients with MM defined by their complementary determining region 3 (CDR3) peak. We further characterize these clones over the disease and subsequent treatment. Second clones were identified by their specific IgH-VDJ sequences that are distinct from those of dominant MM clones. Clonal frequencies were determined through semi-quantitative PCR, quantitative PCR and single-cell polymerase chain reaction of the clone-specific sequence. In 13/74 MM patients, more than one dominant CDR3 peak was identified with 12 patients (16%) being truly biclonal. Second clones had different frequencies, were found in different locations and were found in different cell types from the dominant MM clone. Where analysis was possible, they were shown to have chromosomal characteristic distinct from those of the MM clone. The frequency of the second clone also changed over the course of the disease and often persisted despite treatment. Molecularly-defined second clones are infrequent in monoclonal gammopathy of undetermined significance (MGUS, 1/43 individuals or 2%), suggesting that they may arise at relatively late stages of myelomagenesis. In further support of our findings, biclonal gammopathy and concomitant MM and CLL (chronic lymphocytic leukemia) were confirmed to originate from two unrelated clones. Our data supports the idea that the clone giving rise to symptomatic myeloma exerts clonal dominance to prevent expansion of other clones. MM and second clones may arise from an underlying niche permissive of clonal expansion. The clinical significance of these highly expanded but unrelated clones remains to be confirmed. Overall, our findings add new dimensions to evaluating related and unrelated clonal expansions in MM and the impact of disease evolution and treatment on clonal diversity.